Synonymy of Discotettix adenanii Mahmood, Idris & Salmah, 2007 with D. belzebuth (Serville, 1838) (Orthoptera: Tetrigidae) - Kočárek, Petr; Kuřavová, Kateřina; Musiolek, David; Wahab, Rodzay Abdul; Kahar, Siti Rafhiah Abdul (Zootaxa, 2015)
According to a study of type specimens of Discotettix adenanii Mahmood, Idris & Salmah, 2007 and copious specimens of D. belzebuth (Serville, 1838) collected in different parts of Borneo, we found that all species-specific morphological characters of D. adenanii, according to its original description, fall into the morphological variability of D. belzebuth. Thus, we synonymize D. adenanii with D. belzebuth. The sequence of a segment of the mitochondrial 16S ribosomal RNA of D. belzebuth was also evaluated and added to GenBank as a DNA barcode.